Focal Mechanism and Parameter of Volcano-Tectonic Earthquake Source, in Mount Guntur, West Java - Sri Hidayati; Y. Suparman; A. Loeqman (Indonesian Journal on Geoscience, 2011)
DOI: 10.17014/ijog.v6i1.111Guntur Volcano in West Java is one of the most active volcanoes in Indonesia. The last eruption took place in 1847 and the volcanic activity has been dormant since then, however its seismicity is active. During the period of July to October 2009, the hypocenter distribution of VT earthquakes is mostly located at western flank of the volcano, beneath Guntur - Gandapura craters at the depth of less than 5 km. The depth pattern shows deeper to the northwest. The VT earthquakes deeper than 5 km were not found in this period. The focal mechanism of VT earthquakes are oblique normal fault, strike-slip fault and oblique reverse fault types. The mechanism of those earthquakes is not uniquely determined probably due to complicated structures at Guntur volcano complex area, which is aligned in NW-SE direction. T-axis of the oblique normal fault is trending in northwest - southeast direction similar to the structures found in the summit area of Gunung Guntur Volcano. Similarly, one of the strike-slip fault nodal line and P-axis of oblique reverse fault are also trending in northwest - southeast. Ploting of the earthquake source parameters (seismic moment, corner frequency, and stress drop) made to hypocenter distance shows no significant difference on those parameters between earthquakes at close and far distances to Kabuyutan station. It is probably due to the hypocenters are not concentrated in one zone. Meanwhile, the relationship between seismic moment (Mo) and seismic source radius (r) shows that for earthquakes with moment of smaller than 1018 dyne cm, the radius of the hypocenter is constant which is namely 60 m.